2020
DOI: 10.3897/phytokeys.151.49833
|View full text |Cite
|
Sign up to set email alerts
|

A threatened new species of Ipomoea (Convolvulaceae) from the Brazilian Cerrado revealed by morpho-anatomical analysis

Abstract: A new species of Ipomoea, endemic to the Cerrado domain in Maranhão, Brazil, is described. Ipomoea maranhensis D.Santos & Buril, sp. nov. has been misidentified as I. burchellii Meisn. in several herbaria. Even though both species have oblong, pubescent leaves, they can be distinguished by morpho-anatomical characters. We present a diagnosis, complete description, illustration, taxonomic comments, conservation status and distribution map.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Recent studies in Maranhão have shown that, with increasing sampling effort, new records of Orchidaceae (Ferreira et al 2017(Ferreira et al , 2019aGomes et al 2021;Oliveira et al 2021;Pessoa et al in press) and other plant families (Ferreira et al , 2019bGuarçoni et al 2020b;Silva Júnior et al 2020) are discoverable. Even new species are found in Maranhão, as attested by Scatigna et al (2019), Guarçoni et al (2020a), andSantos et al (2020).…”
Section: Discussionmentioning
confidence: 76%
“…Recent studies in Maranhão have shown that, with increasing sampling effort, new records of Orchidaceae (Ferreira et al 2017(Ferreira et al , 2019aGomes et al 2021;Oliveira et al 2021;Pessoa et al in press) and other plant families (Ferreira et al , 2019bGuarçoni et al 2020b;Silva Júnior et al 2020) are discoverable. Even new species are found in Maranhão, as attested by Scatigna et al (2019), Guarçoni et al (2020a), andSantos et al (2020).…”
Section: Discussionmentioning
confidence: 76%
“…For example, the isobilateral mesophyll was considered a diagnostic trait to differentiate Ipomoea burchellii Choisy from Ipomoea maranhensis D.Santos & Buril (Santos, Arruda, & Buril, 2020), previously considered to be a single species, and the mesophyll is essential to distinguish Evolvulus saxatilis D.Santos and Buril from E. glomeratus Nees & Mart. (Santos, Saraivam, et al, 2020), whose morphological characters also caused them to appear to be the same species. Mesophyll type has also been used to delimit three species of Evolvulus L. (Ketjarun et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Buril from E. glomeratus Nees & Mart. (Santos, Saraivam, et al, 2020), whose morphological characters also caused them to appear to be the same species. Mesophyll type has also been used to delimit three species of Evolvulus L. (Ketjarun et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Matias, 2023). This lower number is probably the result of the lack of extensive sampling efforts in Maranhão focusing on aquatic plants, even though the state is known for its great floristic potential, as evidenced by recent descriptions of new taxa (e.g., Guarçoni et al, 2020;Santos et al, 2020;Silva et al, 2023), and new 1994; Lehtonen, 2008) and the descriptive terminology followed Beentje (2010).…”
Section: Data Collectionmentioning
confidence: 99%